10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
Initiatives to improve physiology majors' social and behavioral professional skills development would be remiss without an understanding of the emotional culture affecting intended audiences. To characterize the emotional hidden curriculum in undergraduate life science education, this study explores feeling rules that influence how undergraduate pre-health students navigate emotional expression-an important aspect of emotional intelligence-in life science classrooms. We conducted semistructured interviews and culturally responsive focus groups at an R1 university in the southeast. Our findings from interviews with 21 students revealed four feeling rules: (1) No feelings allowed - successful scientists suppress emotions, (2) Please them or else - social hierarchies and acceptance take precedence over feelings, (3) Just like me - relatable peers and approachable instructors foster emotional expression, and (4) There's a reason - emotional expression should comply with cultural norms and identity-based expectations. Although pre-health students are aware of the benefits of emotional expression in learning, they perceive a cultural pressure to be emotionally suppressive if they want to maintain a favorable impression and achieve their goals. We highlight implications for biology education research with examples of possible future research areas related to the expansion of social-emotional learning in STEM higher education.